Action research on the development of Chinese communication in a virtual community. Issue 5 (3rd July 2016) - Tang, Joni Tzuchen; Sung, Yao-Ting; Chang, Kuo-En
Abstract : This study was designed to determine if language acquisition can occur in a virtual situation in the absence of explicit instruction. After spending 1 year establishing a virtual community, the authors observed and analyzed interpersonal interactions and the development of Chinese communication competence, communication models, and interaction frequency. The results revealed that (1) language acquisition can be improved autonomously in a virtual situation; (2) communication competence occurs in a loop of processes that include receiving, exploring, dialogue, assimilation, adaptation, asking questions, problem solving, and conversation; (3) social interactions and a friendly environment are the most crucial factors in a virtual community; (4) community consensus, individual motivation, individual personalities, speaking behaviors, language competence, and leading techniques affect how individuals develop communication competence.